(untitled) (Ukrainian Journal of Ophthalmology, 2024)
Cataract surgery is most commonly performed today by utilizing the standardized phacoemulsification technique which results in successful outcomes and low complication rates. At present, most patients undergo cataract surgery in both eyes on separate days, referred to as delayed sequential cataract surgery (DSCS). Immediately sequential bilateral cataract surgery (ISBCS) has emerged as an alternative to traditional DSBCS and is, however, increasingly used in clinical practice throughout the world. The question arises: How safe is ISBCS with respect to postoperative complications?